Intra-Inter Triplet Object Interaction Mechanism in Triplet-Based Hierarchical Interconnection Network - Shahnawaz Talpur; Imran Ali Qureshi; Shahnawaz Farhan Khahro (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Object oriented languages usually avoid direct message passing, due to its complicated implementation, though that is the promising way to communicate in concurrently inherited objects. With the advancement in the high performance computing system, interaction between parallel application objects onto physical cores becomes one of the significant issues, which is not fully explored yet. In object oriented programming attribute data is included in objects and their state can be changed using the methods. Objects enable massage passing to other objects interacting with each other. Comprehensive problems can be molded by object-oriented methodology, and solves difficult program running object-oriented programs.Cores communicate with each other through communicator and groups in MPI, but in our reference architecture TBHIN (Triplet Based Hierarchical Interconnection Network), the cores are already faction in Triplets. We propose IITOIM Model to improve the performance with efficient intra-inter triplet cores communication mechanism between the objects in TBHIN. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2151